DETERMINAN PARITAS DENGAN KEJADIAN HEMORRAGHIA POSTPARTUM DI PUSKESMAS WANASABA - Jusmala Sari; Ni Wayan Supadmi; Ni Nengah Winarni (ProHealth Journal, 2019)
One of the important issues in the field of obstetrics and gynecology is a bleeding problem. Postpartum haemorrhage is the leading cause of death. The purpose of this study was to determine the relationship of parity with the incidence of postpartum hemorrhage in Puskesmas Wanasaba. Digunaka method in this research is descriptive analytic approach Retrospective Study. The population in this study 30 respondents with total sampling technique. The research instrument used is the register book PWS KIA. Data were analyzed using univariate and bivariate and tested using chi square test and hasilnya is P. Value 0.000 <0.05. Based on the results of the 30 respondents who experienced bleeding postparum that primiparous parity as many as 16 people (53.3%) and the least that parity multiparas 5 people (16.7%), while 19 (63.3%) were the most experienced primary postpartum hemorrhage and that at least 11 people (36.7) experienced secondary postpartum hemorrhage. Chi square correlation test stated significance value = 0,000 so that Ho refused and H1 accepted, which means that there is a significant correlation between the two variables. It can be concluded that there is a relationship of parity with the incidence of postpartum hemorrhage in Puskesmas Wanasaba.